Depression and Anxiety in Women Undergoing Therapeutic Abortion: The Effect of Spirituality - Nuray Kurt; Nurdilan Şener Çetin; Ayşegül Demirelli (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objective: This study was conducted to determine the relationship between depression, anxiety, and spirituality levels in women who underwent therapeutic abortion.Materials and Methods: The sample of this descriptive and cross-sectional study consisted of 140 women who underwent therapeutic abortion in a province in eastern Turkey. Data were collected using the “Socio-demographic Form,” “Spirituality Scale,” and “Hospital Anxiety and Depression Scale (HAD).” Cronbach Alpha internal consistency tests, numbers, percentages, t-tests, and correlation tests were used in the analysis of the data.Results: The average age of the women participating in this study was 32.44 ± 9.16, 70% had an education level below high school, 64.3% were not working, 53.6% had not previously had an abortion or miscarriage, and 67.9% had previously given birth.The mean anxiety score for women who had therapeutic abortion was 8.59±3.32, the mean depression score was 8.35±3.27, and the mean Spirituality Scale score was 99.11±16.18. No significant relationship was found between the sub-dimensions of the Spirituality Scale and anxiety in women who had undergone therapeutic abortion. A negative and significant relationship was found between depression and the sub-dimensions of the Spirituality Scale (Spiritual coping, Transcendence, Spiritual experience, Search for meaning, and Total scale scores) in women who had undergone therapeutic abortion. It was found that as women’s depression scores increased, their spirituality scores decreased.Conclusion: This study found no significant relationship between the sub-scales of the Spirituality Scale and anxiety in women who had undergone therapeutic abortion. It was determined that more than half of the women who had undergone therapeutic abortion experienced depression and that there was a relationship between depression and spirituality. Women with high spirituality were found to experience less depression. Based on these results, it may be advisable for women to be assessed for depression by healthcare professionals following therapeutic abortion.